The Crime of Kidnapping - Lamas Puccio, Luis (1986)
The work addresses the crime of kidnapping in its most varied modalities, highlighting it as a highly dangerous antisocial behavior with a growing impact on society. The author points out that although this crime has historically been punished, the 1985 Anti-Kidnapping Law represented a legislative novelty, since it significantly increased the penalties for dealing with this threat. However, it also criticizes the lack of coherence between this legislation and other crimes against freedom, generating problems in its application. In particular, the paper shows that the legislation on the subject lacks technical distinctions to adapt to the various forms of kidnapping and its duration and, in turn, questions the effectiveness of harsher penalties to deter kidnapping, since the results of intimidation are inconclusive. Finally, the author concludes by suggesting the need for a comprehensive and personalized approach to tackle this crime, which tends to place it within the interrelationships, structures and different functions that exist in our society, in order to truly understand what are the causes of the crime of kidnapping.